2013
DOI: 10.1007/s13181-013-0294-y
|View full text |Cite
|
Sign up to set email alerts
|

In the Zzz Zone: The Effects of Z-Drugs on Human Performance and Driving

Abstract: Despite their improved pharmacokinetic profile, the Z-drugs, zolpidem, zopiclone, and zaleplon, have a spectrum of adverse effects comparable to benzodiazepines. This review focuses on the impairment from Z-drugs on cognition, behavior, psychomotor performance, and driving ability. Z-drugs are short-acting GABA agonists that reduce sleep latency without disturbing sleep architecture. Bizarre behavioral effects have prompted warnings on the prescription, dispensation, and use of Z-drugs. Psychomotor impairment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(113 citation statements)
references
References 81 publications
1
106
0
4
Order By: Relevance
“…These are important observations and distinguish gabapentin from various other hypnotic agents, both prescription and OTC, which have been reported to be associated with next-day residual effects. 34,[39][40][41] Overall, there were no clinically meaningful differences in AE frequency or vital sign changes among the three treatment groups. No new safety concerns were identified during the trial.…”
Section: Discussionmentioning
confidence: 85%
“…These are important observations and distinguish gabapentin from various other hypnotic agents, both prescription and OTC, which have been reported to be associated with next-day residual effects. 34,[39][40][41] Overall, there were no clinically meaningful differences in AE frequency or vital sign changes among the three treatment groups. No new safety concerns were identified during the trial.…”
Section: Discussionmentioning
confidence: 85%
“…ZOL and similar drugs like eszopiclone are widely prescribed and generally considered effective at inducing sleep (Greenblatt and Roth, 2012), but their use is associated with a high incidence of adverse effects such as driving impairment (Gunja, 2013;Verster et al, 2006), memory impairment (Balkin et al, 1992;Mintzer and Griffiths, 1999;Wesensten et al, 1995Wesensten et al, , 1996, complex sleep behaviors (Chen et al, 2014;Dolder and Nelson, 2008), and psychomotor deficits (Storm et al, 2007;Wesensten et al, 2005), highlighting the need for hypnotics that induce lessfunctional impairment. ALM and other HcrtR antagonists effectively induce sleep (Brisbare-Roch et al, 2007;Cox et al, 2010) but cause less impairment in memory tasks (Dietrich and Jenck, 2010;Morairty et al, 2014) or motor function in rodents (Ramirez et al, 2013;Steiner et al, 2011), dogs (Tannenbaum et al, 2014), and non-human primates (Uslaner et al, 2013) than do traditional hypnotics.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that Z-drugs have a lower potential for abuse and dependence, 9 their use can also be problematic because of their effects on human performance and driving. 10,11 Because of these potential adverse effects, clinical practice guidelines have advised against the use of benzodiazepines and Z-drugs for longer than 4 weeks, and health agencies worldwide have undertaken anti-benzodiazepine and anti-Z-drug campaigns, not without controversy. [12][13][14][15][16][17][18] However, the dearth of published research studies on this subject suggests that such recommendations have not had a significant impact on the use of benzodiazepines and Z-drugs in various countries.…”
mentioning
confidence: 99%